Beefing up Resistance Onscreen: Cow Politics and Non-vegetarian Carnivals in Post- 2015 Malayalam Films - James, Chithira; Mathew, Reju George (SARE: Southeast Asian Review of English, 2024)
With the rise of Hindutva fundamentalism in India, the hegemony of vegetarianism and the resultant othering of subaltern/non-vegetarian food cultures have intensified. Consequently, Dalits, Adivasis and various religious minorities are being subject to physical and symbolic forms of violence on grounds of their dietary habits. While members of these communities, mostly in the Northern states of India, became victims of lynching by cow vigilantes, acts of resistance termed as ‘Beef Festivals’ were organised across Kerala since 2015. Aided by the peculiar socio-political climate of the state, Malayalam films rapidly assimilated the celebratory/fearless spirit of these festivals of resistance. Reassertion of non-vegetarian culinary traditions, specifically those that are deemed transgressive in the national milieu, by placing them in the political context of Hindutva has become a practice in Malayalam films. By critically looking at select Malayalam films produced in this period, the paper attempts to study the carnivalesque performances in these films and argues that they construct carnival spaces that subvert the food-based hierarchies prevalent in India.